Vessel network architecture of adult human islets promotes distinct cell-cell interactions in situ and is altered after transplantation - Cohrs, C.; Chen, C.; Jahn, S.; Stertmann, J.; Chmelova, H.; Weitz, J.; Bähr, A.; Klymiuk, N.; Steffen, A.; Ludwig, B.; Kamvissi, V.; Wolf, E.; et al. (The Endocrine Society, 2017)
Copyright © 2017 Endocrine Society. Islet-cell hormone release is modulated by signals from endothelial and endocrine cells within the islet. However, models of intraislet vascularization and paracrine cell signaling are mostly based on the rodent pancreas. We assessed the architecture and endocrine cell interaction of the vascular network in unperturbed human islets in situ and their potential to re-establish their endogenous vascular network after transplantation in vivo.We prepared slices of fresh pancreas tissue obtained from nondiabetic patients undergoing partial pancreatectomy. In addition, we transplanted human donor islets into the anterior chamber of the mouse eye. Next, we performed three-dimensional in situ and in vivo imaging of islet cell and vessel architecture at cellular resolution and compared our findings with mouse and porcine islets. Our data reveal a significantly different vascular architecture with decreased vessel diameter, reduced vessel branching, and shortened total vessel network in human compared with mouse islets. Together with the distinct cellular arrangement in human islets, this limits ß to endothelial cell interactions, facilitates connection of a and ß cells, and promotes the formation of independent ß-cell clusters within islets. Furthermore, our results show that the endogenous vascular network of islets is significantly altered after transplantation in a donor agerelated mechanism. Thus, our study provides insight into the vascular architecture and cellular arrangement of human islets with apparent consequences for intercellular islet signaling. Moreover, our findings suggest that human islet engraftment after transplantation can be improved by using alternative, less mature islet-cell sources.